2021
DOI: 10.3346/jkms.2021.36.e228
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Lesion of the Corpus Callosum (CLOCCs) after SARS-CoV-2 mRNA Vaccination

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Although he had recent clinical Lyme disease, we do not believe it explains his MIS-C-like syndrome. Our patient's clinical presentation has similarities with previous reports of CLOCCs in children in the setting of COVID-19 or MIS-C [1], probable myocarditis after COVID-19 vaccination in children [14][15][16], and CLOCC in a previously healthy young male after initial COVID-19 mRNA vaccination [17].…”
Section: Discussionsupporting
confidence: 82%
“…Although he had recent clinical Lyme disease, we do not believe it explains his MIS-C-like syndrome. Our patient's clinical presentation has similarities with previous reports of CLOCCs in children in the setting of COVID-19 or MIS-C [1], probable myocarditis after COVID-19 vaccination in children [14][15][16], and CLOCC in a previously healthy young male after initial COVID-19 mRNA vaccination [17].…”
Section: Discussionsupporting
confidence: 82%
“…To the best of our knowledge, this is the first report of neurological manifestations with CLOCCs that occurred approximately 1 week after COVID-19 vaccination. Thus far, 2 case reports showed that CLOCCs emerged 2 or 3 days after COVID-19 vaccination [11,12]. On the other hand, Patient 1 in our study demonstrated that MRI on Day 9 was negative for the splenial lesion and CLOCCs was noticed on Day 18, and IL-6 elevation in the CSF.…”
Section: Discussionmentioning
confidence: 43%
“…[1][2]7 It is important to notice that CLOCCs have been recently associated with COVID-19 and SARS-CoV-2 mRNA vaccine (BNT162b). [3][4] To our knowledge, this is the second case of CLOCCs after SARS-CoV-2 vaccination described in the literature. Fever is usually a prodromic manifestation and is accompanied by headache.…”
Section: Discussionmentioning
confidence: 76%
“…In this case, initial symptoms have started 2 days after SARS-CoV-2 mRNA vaccine, a finding consistent with the data reported by Youn et al, who reported a case of cytotoxic lesions of the corpus callosum 3 days after BNT162b vaccine. 3 As regards CLOCCs correlated to other vaccinations, only mumps vaccination has been previously associated with CLOCCs and some authors have reported that the onset of symptoms ranged from 13 to 21 days after mumps vaccination, likely to the incubation period of mumps infection. 8 - 9 Typical MRI characteristics demonstrate a transient and reversible hyperintense lesion on long TR sequences in the corpus callosum, associated with restricted diffusion on diffusion-weighted images (DWIs).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation